Genetic profile of sports climbing athletes from three different ethnicities - Saito, M.; Ginszt, M.; Semenova, E.; Massidda, M.; Huminska-Lisowska, K.; Michalowska-Sawczyn, M.; Homma, H.; Cieszczyk, P.; Okamoto, T.; Larin, A.; Generozov, E.; Majcher, P.; et al. (Biology of Sport, 2022)
This study aimed to investigate the ACTN3 R577X, ACE I/D, CKM rs8111989, and TRHR rs7832552 genotypes in climbers and controls in three ethnicities. The study consisted of 258 climbers (Japanese, n = 100; Polish, n = 128; Russian, n = 30) and 1151 controls (Japanese: n = 332, Polish: n = 635, Russian: n = 184). Genotyping results were analyzed using the TaqMan approach in Japanese and Polish subjects and HumanOmni1-Quad Bead Chips in Russian subjects. There were no significant differences in ACTN3 R577X and ACE I/D polymorphism distribution between climbers and controls in any ethnic cohort or model. The frequencies of the C allele in the CKM polymorphism and the T allele in the TRHR polymorphism were higher in climbers than in controls only in the Russian cohort (p = 0.045 and p = 0.039, respectively). The results of the meta1analysis on three cohorts showed that the frequency of XX+RX genotypes in the ACTN3 R577X polymorphism was significantly higher in climbers than that in the controls (p = 0.01). The X allele of the ACTN3 R577X polymorphism was associated with sport climbing status, as assessed using a meta-analysis of climbers across three different ethnicities.